PENGARUH EFEKTIVITAS PENGENDALIAN INTERNAL, KESESUAIAN KOMPENSASI, MORALITAS MANAJEMEN, KETAATAN ATURAN AKUNTANSI, DAN ASIMETRI INFORMASI TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI (Studi Kasus Pada Kantor BKAD Kota Malang) - Indara Handayani; Noor Shodiq Askandar; Dwiyani Sudaryanti (Universitas Islam Malang, 2021)
This study aims to determine the effect of Internal Control Effectiveness, Compensation Suitability, Management Morality, Compliance with Accounting Rules, and Information Asymmetry on the Trend of Accounting Fraud. The case study in this research is at the Malang City BKAD office. Data collection in this study used purposive sampling method. Analysis of the data used using multiple linear regression test. The results of this study partially, namely the effectiveness of internal control variables have a negative and significant effect on the tendency of accounting fraud. The compensation suitability variable has a negative and significant effect on the tendency of accounting fraud. The variable of management morality has a negative and significant effect on the tendency of accounting fraud. The variable of obedience to accounting rules has a negative and significant effect on the tendency of accounting fraud. Information asymmetry variable has a negative and significant effect on the tendency of accounting fraud.Keywords: Internal Control, Compensation, Management Morale, Accounting Rules, Accounting Fraud